KARAKTER MORFOLOGI DAN POLA PERKECAMBAHAN BIJI Strombosia javanica Bl. (Olacaceae) DALAM KAITANNYA DENGAN SIFAT-SIFAT PARASITISME [Morphological Characters and Germination Patterns of Strombosia Javanica Bl. (Olacaeae) Associated with Parasitism] - Rachman, Erlin; Sunaryo, Sunaryo (Research Center for Biology-Indonesian Institute of Sciences, 1999)
A study on seed germinations of Strombosia javanica BL. was conducted to observe morphological character and germination pattern of the seedling. As many as 134 seeds of the species, originally collected in Bogor Botanical Gardens, were germinated on medium contain soil, sands and compost in same quantity. Germination aspects such as germination patterns and developmental changes were monitored everyday until the first leaves appear. The seed germinations was typically hypogeal and totally spent 160-170 days, and consisted at least six stages: hypocotyl growth, radix primordial formatton, seedling root growth, seed ball lifting, seed ball removal and first leaves appearance. Rather intact seed ball remain exist at the end of hypocotyl vigorously mtil its removal, pmsumably one of special phenomena of the species germination associated to plant parasitism. Functionally, development of the cotyledons were abnormally suppressed by the existence of the seed ball. The cotyledon praphotosynthetic function seems to be replaced by greeny hypocotyl. First leaves development were never occurred before the seed ball removal. Seed coat elimination was able to increase germination initiation in a given time but facilitated damaging bacteria or fungi to contaminate the endosperm.